Studies on Morphological Evolution of Gravure-Printed ZnO Thin Films Induced by Low-Temperature Vapor Post-Treatment - Giuliano Sico; Vincenzo Guarino; Carmela Borriello; Maria Montanino (Nanomaterials)
In recent years, the morphology control of semiconductor nanomaterials has been attracting increasing attention toward maximizing their functional properties and reaching their end use in real-world devices. However, the development of easy and cost-effective methods for preparing large-scale patterned semiconductor structures on flexible temperature-sensitive substrates remains ever in demand. In this study, vapor post-treatment (VPT) is investigated as a potential, simple and low-cost post-preparative method to morphologically modify gravure-printed zinc oxide (ZnO) nanoparticulate thin films at low temperatures. Exposing nanoparticles (NPs) to acidic vapor solution, spontaneous restructuring pathways are observed as a consequence of NPs tending to reduce their high interfacial energy. Depending on the imposed environmental conditions during the treatment (e.g., temperature, vapor composition), various ZnO thin-film morphologies are produced, from dense to porous ones, as a result of the activation and interplay of different spontaneous interface elimination mechanisms, including dissolution–precipitation, grain boundary migration and grain rotation–coalescence. The influence of VPT on structural/optical properties has been examined via XRD, UV–visible and photoluminescence measurements. Controlling NP junctions and network nanoporosity, VPT appears as promising cost-effective, low-temperature and pressureless post-preparative platform for preparing supported ZnO NP-based films with improved connectivity and mechanical stability, favoring their practical use and integration in flexible devices.